A Study of Idioms Containing Color Words in English and Vietnamese - Nguyễn Thị Diệu Hảo (2005)
This is a contrastive analysis of English and Vietnamese idioms containing color words. The analysis is carried out not only to find out similarities and differences in syntax and sematic fields, but also to discover and contrast typical cultural characteristics of these kinds of color idioms, figurative meanings of their color words and origins of some of the color idioms. The thesis also suggests some implications for the teaching and learning of idioms in general, and for the translating of color idioms from English into Vietnamese and vice versa in particular.